PENGELOLAAN SEKOLAH BERBASIS FILANTROPI (Studi Situs di SMK Gratis Smart Informatika Surakarta) - Subando, Joko (Kopertais Wilayah X Jawa Tengah, 2016)
AbstractTh e purpose of this study is to describe the management of school-based philanthropy on SMK Gratis Smart Informatika Surakarta. Th e study used a qualitative approach to the design of ethnography. Data were collected through observation, documentation and in-depth interviews with a variety of sources, Solopeduli Foundation, Principal, Vice Principal, Teachers, Employees, Students and Parents Students. Th e information collected is around management of schools ranging from school strategic plans, operational plans, school programs, fund management, human resources, learning management, monitoring, evaluation, and so forth. Th e data has been collected and then analyzed with a model Miles-Hubberman. Th e results showed that the presence of Solopeduli foundation as Islamic philanthropic institutions to make the school as a unit management program has a distinctive character that sharia management. Poverty, sincerity and concern used as view point institutions in organizing employees, equalizing step, build unity and establish sincerity in work. Donors, donations, and the mandate of the donors is said lighter so that raises self control and supervision of the divine. Th is is what makes the activities run e? ectively and e? sient. School explore alms, Tah? dz, mentoring and make it as an entry point to build and deliver school Spiritual intelligence to the summit of achievement.Keyword: management, schools, philanthropy